Toxicological evaluation of transgenic rice flour with a synthetic cry1Ab gene from Bacillus thuringiensis - Wang, Zhong‐hua; Wang, Yin; Cui, Hai‐rui; Xia, Ying‐wu; Altosaar, Illimar; Shu, Qing‐yao (Society of Chemical Industry, 2002)
Bacillus thuringiensis (Bt) transgenic (KMD1) and non-transgenic (KMD1's parental variety Xiushui 11) rice flours were assessed in a 90 day feeding test with rats. KMD1 contained a synthetic cry1Ab gene from Bt, and selection marker genes nptII and hpt linked in tandem. In the ≤64g kg-1 body weight (BW) dosage range (Bt transgenic rice flour composed 64% of the ingredients of the diet), no adverse effects of Bt rice on rats were observed in terms of animal behaviour, weight gain and feed utilisation rate. Necropsy at the end of the experiment indicated that neither pathological lesions nor histopathological abnormalities were present in organs such as liver, kidneys, intestines and testes of rats in both test and control groups by macroscopic and microscopic pathology. In addition, no significant differences (P > 0.05) were observed in relative organ weights, haemograms and blood indices of rats between test and control groups. Several serum parameters of female rats were found to be significantly different between Bt and non-Bt diets, but the values of these parameters were still within the normal ranges of values for rats of this age and sex. These results demonstrated that Bt rice flour at a dosage of 64g kg-1 BW, Bt toxin and NPTII and HPT proteins have no toxic effects on rats.